Literature Study: The Effect of Abdominal Massage to Reduce Gastric Residual Volume in Critically Ill Patients - Adella Indri Afitasari; Dian Hudiyawati (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
Gastrointestinal dysfunction is one of the most common problems experienced by patients in the ICU, such as abdominal distension, constipation, and increased gastric residual volume. Currently, non-pharmacological interventions have been developed to address these problems. Abdominal massage intervention is considered a method that can improve digestive function. The purpose of this literature study was to determine the effect of abdominal massage to reduce the gastric residual volume in critically ill patients. Selected articles were obtained through online databases such as PubMed, Google Scholar, and ScienceDirect. There were seven articles obtained after going through screening and identified for critical review. There were five study randomized controlled trials, three quasi-experimental designs, one study, one group pre-test post-test, and one article one-shot case study. The results of this study found that abdominal massage was effective in reducing gastric residual volume. Mechanism of abdominal massage with stimulation of peristalsis, changes in intra-abdominal pressure, mechanical and reflexive effects on the intestine, thereby shortening the transition time of food in the intestine, increasing bowel movements, and easier flow of food through the digestive tract. So that nurses in the ICU are expected to use abdominal massage as an intervention option at critical times, considering that this intervention can prevent gastrointestinal dysfunction with low risk and is cost-effective.